Improving shared decision-making in advance care planning: Implementation of a cluster randomized staff intervention in dementia care. Issue 4 (April 2020) - Goossens, Bart; Sevenants, Aline; Declercq, Anja; Van Audenhove, Chantal
Highlights: Nursing home professionals benefit from training in shared decision-making. Benefits include a higher realization of shared decision-making in practice. Perceptions of competence and importance increase. These changes occur without increased time spent in discussions. Staff turnover and cooperation with GP's remain barriers to shared decision-making. Abstract: Objective: Increasing staff engagement level of shared decision-making in advance care planning for persons with dementia in nursing homes. Perceived importance, competence and frequency of staff members applying shared decision-making were measured. Additionally, facilitators and barriers in the implementation process were described. Methods: In this pretest-posttest cluster randomized trial, 311 staff members from 65 Belgian nursing home wards participated. Key components of the intervention were knowledge on shared decision-making, role-play exercises and internal policies on advance care planning. Audio recordings of advance care planning conversations between residents, families and staff were compared before and after the intervention. Participants filled in questionnaires and provided feedback. Results: Wards demonstrated a higher level of shared decision-making after the intervention (p < 0.001) while time spent on the conversations did not increase. This effect persisted at 6 months follow-up (p < 0.001). Participants perceived shared decision-making as more important (p = 0.031) and felt more competent (p = 0.010), though frequency of use did not change (p = 0.201). High staff turnover and difficult co-operation with GP's were barriers. Conclusion: Nursing home staff benefits from this training in shared decision-making. Practice implications: Learning shared decision-making in advance care planning for persons with dementia is possible and sustainable in the time-constricted context of nursing homes.